Views on wet nursing and expressing breastmilk for sharing and human milk bank donation among mothers in two parenting social media communities in Vietnam - Tuan T. Nguyen; Ngoc L. Huynh; Genevieve Becker; Hoang T. Tran; Jennifer Cashin; Roger Mathisen (Maternal and Child Nutrition)
Abstract Nutrition in early life plays a key role in shaping an infant's future health. There is limited understanding of the perspectives of Vietnamese mothers with children under 24 months of age regarding breastmilk expression, donation and use. In this cross‐sectional study, an online survey was administered through two parenting social media communities to assess opinions on breastmilk expression, breastmilk donation including contributions from bereaved mothers and the use of donor human milk. A 4‐point Likert scale was used to evaluate respondents' opinions, and demographic and breastfeeding information was collected. Among 375 respondents, almost 30% had received breastmilk from another woman, either through direct breastfeeding (14.7%), expressed breastmilk (12.5%) or from a human milk bank (2.7%). In this survey of 375 mothers, 84.0% indicated they would store excess breastmilk, while 75.7% and 69.6% would donate to a human milk bank or another mother, respectively. When faced with insufficient breastmilk, 88.5% of mothers would seek ways to increase supply, whereas 23.8% considered using commercial milk formula. Regarding milk expression among the 375 mothers, 78.4% preferred electric pumps, compared to 48.6% for manual pumps and 45.9% for hand expression. Additionally, 80.5% of the 375 mothers would suggest donating stored milk to bereaved peers and 85.6% would suggest mothers with mild COVID‐19 to continue breastfeeding with precautions. These findings indicate that this sample has positive views on breastfeeding, breastmilk donation and the use of donor human milk.